Novel CDKN2A mutations in Austrian melanoma patients. Issue 5 (October 2015) - Burgstaller-Muehlbacher, Sebastian; Marko, Martha; Müller, Christoph; Wendt, Judith; Pehamberger, Hubert; Okamoto, Ichiro
<x xml:space="preserve">Abstract</x> CDKN2A is the most prominent familial melanoma gene, with mutations occurring in up to 40% of the families. Numerous mutations in the gene are known, several of them representing regional founder mutations. We sought to determine, for the first time, germline mutations in CDKN2A in Austria to identify novel mutations. In total, 700 individuals (136 patients with a positive family history and 164 with at least two primary melanomas as the high-risk groups; 200 with single primary melanomas; and 200 healthy individuals as the control groups) were Sanger sequenced for CDKN2A exon 1α, 1β, and 2. The 136 patients with affected relatives were also sequenced for CDK4 exon 2. We found the disease-associated mutations p.R24P (8×), p.N71T (1×), p.G101W (1×), and p.V126D (1×) in the group with affected relatives and p.R24P (2×) in the group with several primary melanomas. Furthermore, we discovered four mutations of unknown significance, two of which were novel: p.A34V and c.151−4 G>C, respectively. Computational effect prediction suggested p.A34V as conferring a high risk for melanoma, whereas c.151−4 G>C, although being predicted as a splice site mutation by MutationTaster, could not functionally be confirmed to alter splicing. Moreover, computational effect prediction confirmed accumulation of high-penetrance mutations in high-risk groups, whereas mutations of unknown significance were distributed across all groups. p.R24P is the most common high-risk mutation in Austria. In addition, we discovered two new mutations in Austrian melanoma patients, p.A34V and c.151−4 G>C, respectively.